The Fierce Tribe - Weems, Mickey (Utah State University, University Libraries, 2008)
In this ethnography that documents the folk nature of popular culture, Mickey Weems applies interdisciplinary interpretation to a subject that demands such a breakdown of intellectual boundaries. The Circuit, an expression of gay culture, comprises large dance events